2021
DOI: 10.1038/s41598-021-96075-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use/land cover changes on water quality and human health in district Peshawar Pakistan

Abstract: The quality and quantity of groundwater resources are affected by landuse/landcover (LULC) dynamics, particularly the increasing urbanization coupled with high household wastewater discharge and decreasing open lands. This study evaluates temporal changes of groundwater quality for 2012 and 2019, its relation to Landuse/landcover, and its impact on Peshawar's residents (study area), Pakistan. A total of 105 and 112 groundwater samples were collected from tube wells in 2012 and 2019. Samples were then analyzed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 60 publications
2
21
0
4
Order By: Relevance
“…It was shown that this expansion primarily occurred at the expense of areas that were previously planted with crops or were open bare land. Expansion of built-up areas at the expense of cropland during the process of urbanization has also been noted in other Pakistani metropolises, including Lahore [63], Peshawar [64], and Islamabad [65]. An important feature observed concerning LULC changes in Karachi during 2000-2020 was that the cropland and open bare land were first converted into areas of open land before becoming part of the built-up area.…”
Section: Discussionmentioning
confidence: 80%
“…It was shown that this expansion primarily occurred at the expense of areas that were previously planted with crops or were open bare land. Expansion of built-up areas at the expense of cropland during the process of urbanization has also been noted in other Pakistani metropolises, including Lahore [63], Peshawar [64], and Islamabad [65]. An important feature observed concerning LULC changes in Karachi during 2000-2020 was that the cropland and open bare land were first converted into areas of open land before becoming part of the built-up area.…”
Section: Discussionmentioning
confidence: 80%
“…However, surface recharge, water runoff, weathering processes, and industrial effluents can all contribute to increased turbidity in the area’s water system. Furthermore, excessive turbidity can be caused by shallow and poorly designed wells [ 46 ]. The value of HCO 3 − varied between 143 and 532 mg/L, with an average value of 289.5 mg/L, and was beyond the permitted limit of WHO.…”
Section: Resultsmentioning
confidence: 99%
“…Land use land cover data has been further analyzed for key land use land cover features classes. Agriculture, built up, forest, barren land and wetland were taken as the key land use land cover features of the area (Ahmad et al, 2021;Lockhart et al, 2013). Most of the subclasses were merged with these key land use land cover classes.…”
Section: Percentage Depletion In Water Levels From Base Year 2005mentioning
confidence: 99%
“…The work also shows a detailed investigation of the mentioned urban area. The present paper can be an eye-opener for the interdependence of groundwater and urbanisation among urban policy-makers to provide a framework for systematic consideration of groundwater in urban management (Ahmad et al, 2021).…”
Section: Relationship Between Changes In Agriculture and Water Levelsmentioning
confidence: 99%